Acritarchs from the Duolbagáisá Formation (Cambrian Series 2-Miaolingian) on the Digermulen Peninsula, Finnmark, Arctic Norway: towards a high-resolution Cambrian chronostratigraphy - Palacios, Teodoro; Högström, Anette; Ebbestad, Jan Ove R.; Agić, Heda; Høyberget, Magne; Jensen, Sören; Meinhold, Guido; Taylor, Wendy L. (Geological Magazine, 2020)
New information on acritarchs from the Duolbagáisá Formation, Digermulen Peninsula, Arctic Norway, enable recognition of the three Cambrian Series 2 acritarch-based zones: the Skiagia ornata–Fimbriaglomerella membranacea, Heliosphaeridium dissimilare–Skiagia ciliosa and Volkovia dentifera–Liepaina plana Assemblage zones. Acritarchs of the Skiagia ornata–Fimbriaglomerella membranacea Zone (Cambrian Stage 3) appear near the base of the unit, close to an undetermined trilobite. In the Upper Member of the Duolbagáisá Formation, in levels with Kjerulfia n. sp. and Elliptocephala n. sp., appears an assemblage with abundant Skiagia ciliosa , indicative of the Heliosphaeridium dissimilare–Skiagia ciliosa Zone. A few metres higher appear Liepaina plana, Heliosphaeridium notatum and Retisphaeridium dichamerum , which indicate the Volkovia dentifera–Liepaina plana Zone (Cambrian Stage 4). The transition between the Duolbagáisá Formation and the overlying Kistedalen Formation is marked by the appearance of Comasphaeridium longispinosum, Multiplicisphaeridium llynense and Eliasum llaniscum , diagnostic of the Miaolingian Series. This coincides with the disappearance of Skiagia occurrences of Skiagia in Miaolingian strata consist of reworked material related to the Hawke Bay regression at the Cambrian Stage 4–Wuliuan transition. The absence of Skiagia in higher levels of the Duolbagáisá Formation and Kistedalen Formation suggests that no unconformity formed during the Hawke Bay regression in this area. The chronostratigraphical significance of the Skiagia ornata–Fimbriaglomerella membranacea, Heliosphaeridium dissimilare–Skiagia ciliosa and Volkovia dentifera–Liepaina plana zones is critically analysed. Correlation of the Duolbagáisá Formation with peri-Gondwanan terrains of Avalonia and Iberia is established. The Digermulen Peninsula has great potential as a reference section for establishing a Cambrian chronostratigraphy based on acritarchs.